2013
DOI: 10.1128/ec.00086-13
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Regulated Glycosome Protein Composition in the African Trypanosome

Abstract: Trypanosomes compartmentalize many metabolic enzymes in glycosomes, peroxisome-related microbodies that are essential to parasite survival. While it is understood that these dynamic organelles undergo profound changes in protein composition throughout life cycle differentiation, the adaptations that occur in response to changes in environmental conditions are less appreciated. We have adopted a fluorescent-organelle reporter system in procyclic Trypanosoma brucei by expressing a fluorescent protein (FP) fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…), glycosome composition (Bauer et al. ) and the requirement for glycosome protein import in the PCF parasite (Furuya et al. ) is influenced by extracellular glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…), glycosome composition (Bauer et al. ) and the requirement for glycosome protein import in the PCF parasite (Furuya et al. ) is influenced by extracellular glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in glycosome composition can be monitored via following cellular fluorescence. Using this system, we have found that environmental conditions, notably glucose, regulate glycosome composition 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The sequence encoding the fusion protein is cloned into pXS2bla 12 , which contains the procyclin promoter and the tubulin intergenic regions, which direct homologous recombination into the genome and the blasticidin resistance gene for selection. Procyclic cell lines harboring the genes encoding the T7 polymerase and tetracycline repressor (PF29-13) are transformed with the targeting construct, pXS2:PTS2eYFP.…”
Section: Transfection Of Pcf Parasites With the Fluorescent Reporter mentioning
confidence: 99%
“…Cells were harvested (5×10 7 , 800 g 10 min), washed three times with PBS, and fixed (2% paraformaldehyde, 2.5% glutaraldehyde in 100mM phosphate buffer pH 7.4). Cells were stored at 4°C for no longer than 2 days before being processed as described previously ( 23 ). Glycosome area measurements were performed using FIJI.…”
Section: Methodsmentioning
confidence: 99%